Quantitative evaluation of groundwater and surface water interaction characteristics during a dry season. (5th June 2021) - Jia, Sida; Dai, Zhenxue; Du, Xinqiang; Meng, Bo; Yang, Zhijie; Lan, Tianshan
Abstract: The groundwater‐surface water interaction (GSI) is one of the key issues for the sustainable management of the ecological environment and agricultural production. This study developed an integrated approach combining hydrochemical data interpretation via multivariate statistics and stable isotope analysis for the quantitative evaluation of the GSI characteristics. Through field hydrogeological investigation and sampling, hierarchical cluster analysis (HCA) and principal component analysis (PCA) of water chemistry parameters and isotopic tracers have been conducted to identify the areas and properties of GSI across spatial scales. As the geological and hydrogeological conditions in the seasonal frozen area are complex and affected by human activities and winter freezing and thawing, the GSI in the dry season had obvious segmentation, and the GSIs were different on both sides of some reaches. The outcomes of Q‐mode HCA and PCA indicated that EC and redox conditions are the main identification factors of hydrochemistry of groundwater and GSI. The results from this study provided insightful information for us to understand the major impact factors of GSI, as well as the water resources distributions.